Monday

April 21, 2014

April 21, 2014

Posted by **lilly** on Wednesday, March 27, 2013 at 1:15am.

f^-1(x)=

I haven't one clue how to do this...help me pleaaaase someone!

- math -
**Reiny**, Wednesday, March 27, 2013 at 7:46amlet y = (2x+8)/(3x-7) , notice the brackets are essential

step1: interchange the x and y variables to form the initial inverse.

x = (2y+8)/(3y-7)

step: solve this new equation for y

3xy - 7x = 2y+8

3xy - 2y = 7x + 8

y(3x - 2) = (7x + 8)

y = (7x + 8)/(3x - 2)

f^-1 (x) = (7x + 8)/(3x - 2)

test with some value of x, say x = 3

f(3) = 14/2 = 7

f^-1 (7) = should get 3 back ..

= (49+8)/(21-2) = 57/19 = 3 , looks ok

**Related Questions**

Algebra2 - Complete parts a c for each quadratic function: a. Find the y-...

?? Maths?? - Find the values of b and c for which x^2+bx+c is a factor of 2x^3-...

Math - 2x^3 + 3x^2 + x + 1 dx --------------------- -2x + 1 [2x^3 + 3x^2 + x...

math - So is the function, f(x)= 2x- 3x + 4 linear or nonlinear? Find f(-3) ...

math! - about finding the inverse of y=(2x+1)/(x+3). should you multiply (x+3) ...

Algebra-One to one function - Could you please check my answers and help me with...

Math help - How do you do these questions, I have all my steps done until the ...

Math - How do you do these questions, I have all my steps until the last one: 2x...

Math - How do you do these questions, I have all my steps done until the last ...

Math Ms Sue check - How do you do these questions, I have all my steps done ...